Does E-wallet Adoption Affect the Productivity of SMEs in Labuan?: A Bibliometric Approach - Suzanira Zainia; Suzillah Sidek (Faculty of Business, Economics and Accountancy Universiti Malaysia Sabah, 2023)
An obvious increase in e-wallet adoption was seen during the COVID-19 outbreak as society felt more convenient using e-wallet to exercise social distancing while making transactions. To stay competitive and relevant, SMEs was pressured to adopt e-wallet. The process of moving into a new transaction method definitely difficult especially for SMEs which are frequently a few steps behind in technology development thus this study aims to understand the e-wallet adoption among SMEs and it affect towards productivity. However, past literature related with e-wallet adoption is only focusing on the e-wallet user whose is the buyer in economic cycle and hardly any paper considering the adoption from the sellers’ view. Hence, using the bibliometric approach, this research aims to understand the trend of e-wallet adoption. The two main objectives of this paper are i) to determine the factors influenced the adoption behaviour of e-wallet among SMEs and ii) to determine the relationship between e-wallet adoption and the organization’s productivity of SMEs. Based on our analysis, we find that all six exogenous variables - peformance expectancy, effort expectancy, social influence, facilitating condition, perceived risk and perceived cost are significant positive with the adoption of e-wallet. Next, our review also shows that adoption behaviour indeed has a positive impact towards the endogenous variable of organization’s productivity. The findings from this paper will study and discuss the trend from past studies as well as future research trends. In conclusion, this paper will definitely help scholars understand more about the evolution of e-wallet adoption research from a bibliometric perspective especially related with sellers’ viewpoint.